Avaliação do desempenho ambiental, energético, termomecânico e microestrutural de estruturas de concretos sustentáveis submetidas a ambiente marinho - Bichinho , Melina Cavalcanti de Melo (2019)
When it comes to construction, Portland cement and its variations are the protagonist materials of the activity. It is the main component of concrete and mortar that serve as the foundation for the construction of various types of buildings, especially those subjected to the marine environment. However, for some time, its production process has been questioned by the researchers due to the significant environmental impacts caused by the high release of CO2 during its manufacturing process. In parallel and in an attempt to mitigate such impacts, other material alternatives have been developed and improved over the years, such as alkaline activated material cement. Thus, the objective of this work is to evaluate the environmental and energy performance of concrete structures based of alkaline activated material submitted to marine environment and compare to Portland cement-based concrete, as well as to compare their thermomechanical properties and correlate it with their microstructural characteristics. For this research, 60 specimens were prepared, including Portland cement concrete and alkaline activated material submitted to curing in natural and marine environment and evaluated at 3 different ages (7, 28 and 56 days). The properties and microstructures of the specimens were accessed via Simple Compression Strength, X-Ray Diffraction (XRD), Fourier Transform Infrared Spectroscopy (FTIR), Thermogravimetry (TG) and Scanning Electron Microscopy (SEM) analyzes. For environmental impact assessment, the Simapro Software was used to perform CO2-eq emission calculations. After the analysis, was observed the efficiency of the alkaline-activated concrete on the mechanical strength (up to 50% higher) and thermal stability at elevated temperatures (1000oC), as well as lower CO2-eq emission in the atmosphere (36% lower) and energy demand (63% lower) for its production when compared to the Portland cement concrete. Alkaline activated material also confirms the preservation of its microstructural characteristics when exposed to the marine environment, thus making it a good binder alternative for civil construction, especially regarding sustainability.